Maqashid Syariah dan Fatwa MUI: Dampak Prohibisi Salam Antaragama terhadap Keseimbangan Keluarga dan Keharmonisan Multireligius: Maqasid al-Shariah and its Implications for Multicultural Families in Indonesia - Encep Taufik Rahman; Muharir Muharir; Hisam Ahyani; Nurul Ilyana Muhd Adnan (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
The fatwa issued by the Indonesian Ulema Council (MUI) on the prohibition of interfaith greetings by Muslims has triggered significant discourse in the context of Indonesia's religiously and culturally plural society. This research aims to analyze the theological basis of the fatwa and its socio-cultural implications, especially in the context of multicultural families, through the maqasid syariah approach. Using a qualitative method based on content analysis, this research examines fatwa documents and related literature that discuss Islamic legal theory and interfaith social dynamics. The results show a tension between the principle of hifz al-din (protection of religion) and the goals of adl (justice) and maslahah (public welfare), especially since the implementation of this fatwa has the potential to cause emotional tension, social fragmentation, and decreased cohesion in interfaith families and communities. This study confirms that a normative and rigid theological approach, if it does not consider socio-cultural realities, can hinder efforts to build interfaith harmony. Therefore, a contextual and dialogical approach is needed in the stipulation of fatwas so that they are in line with the lived experience of Muslims in pluralistic societies. These findings provide conceptual and practical contributions to the development of Islamic fiqh that is more inclusive and adaptive to social diversity in Indonesia.